(untitled) (Prilozi za orijentalnu filologiju, 2025)
It was of great importance for the Ottoman authorities to establish a fast, secure, and regular postal connection between Istanbul, Bosnia, and other administrative centers. On the main trade routes, special postal stations, menzilhane, were built at intervals of approximately from each other ten hours of walking. The menzilhane were leased for one year, which also marked the duration of the appointed menzilci’s mandate – an official and/or lessee who supervised the entire operation of the menzilhane. This paper presents a yearly expense report of the Sarajevo menzilhane from the late 18th century, based on a sicill (court record) from the Sarajevo Sharia Court for the specified period, which is kept in the Gazi Husrev-beg Library in Sarajevo. The expense report covers various expenditures of the menzilhane, including its maintenance, lease price, and other business costs. One-third of these costs were covered by the Nahiya of Visoko, while the remaining two-thirds were paid by the surrounding villages of the Nahiya of Sarajevo.